SPICE modeling and performance analysis of EnhancementMode GaN HEMT for augmented hard-switching energy conversion efficiency - Liu, Xinzhi; Shafie, Suhaidi; Mohd Radzi, Mohd Amran; Azis, Norhafiz; Norddin, Nurbahirah; Lawal, Ismail; Zulkifli, Normaziah; Abdul Karim, Abdul Hafiz (Universiti Putra Malaysia Press, 2024)
The advancement of renewable energy sources necessitates the development of effective power electronic devices. Enhancement-mode Gallium Nitride (E-GaN) high-electronmobility transistors (HEMTs), an emerging wide-bandgap semiconductor device, demonstrate potential in photovoltaic (PV) energy converting applications to enhance power transfer efficiency. This paper discusses the enhanced semiconducting characteristics of GaN HEMT over conventional silicon power devices by analyzing spontaneous and piezoelectric polarizations of wurtzite GaN crystalline structure and the formation of two-dimensional electron gas (2DEG). The lateral device structure of E-GaN HEMT and normally switched-on depletion mode GaN HEMT are compared. A device-under-test (DUT) equivalent model incorporating parasitic components is proposed, adopting the EPC2204 Level 3 SPICE model. The model is simulated in a novel Double Pulse Test (DPT) topology with clamping and snubber subcircuits using LTSPICE software. The performance of GaN E-HEMT is compared to a MOSFET with similar parameters, and the impact of parasitic inductances and stray capacitances is evaluated through switching analysis. Findings support the potential of E-GaN HEMTs and indicate the DC-DC converter design considerations for portable solar PV system applications. © Universiti Putra Malaysia Press.